Endoscopic treatment of Zenkerʼs diverticulum by complete septotomy: initial experience in 19 patients - Juin, Charlotte; Barret, Maximilien; Belle, Arthur; Abouali, Einas; Leblanc, Sarah; Oudjit, Ammar; Dohan, Anthony; Coriat, Romain; Chaussade, Stanislas (Endoscopy International Open, 2020)
Background and study aims Endoscopic treatment of Zenker’s Diverticulum (ZD) using a flexible endoscope and a diverticuloscope consists of myotomy of the cricopharyngeus muscle, sparing the lower part of the diverticular septum. However, recurrence occurs in up to 54 % of patients at 4 years. We assessed the feasibility and safety of a complete septotomy in endoscopic treatment of ZD.Patients and methods We conducted a retrospective analysis of a prospectively collected database at a single referral center. All consecutive patients treated by complete resection of the diverticular wall were included. The endoscopic technique used a distal attachment cap and division of the ZD septum using a Dual Knife or a Triangle Tip knife in endocut mode, until the esophageal muscularis propria was seen and no residual diverticulum remained. Symptoms were evaluated using the Augsburger questionnaire.Results Nineteen patients, 10 of whom were men with mean age 79 ± 12 years, were treated by complete septotomy for a symptomatic ZD with a median size of 2.5 cm (range 1–5 cm). The clinical success rate was 100 % and the complication rate was 10 % (one pneumonia and one atrial fibrillation). Median hospital stay was 2 days (range 1–3 days). On Day 1 esophagogram, no extraesophageal contrast leakage was seen, periesophageal CO2 was still visible in two patients, and complete ZD regression was seen in 63 % of patients. The 6-month clinical success rate was 100 %, with two patients lost to follow-up, and a median symptom score of 0 (range 0–4). After a mean ± SD follow-up of 9 ± 5 months, the clinical success rate was 94 % (16/17).Conclusion Complete endoscopic septotomy is a feasible and safe therapeutic modality in patients with symptomatic ZD that does not require use of a diverticuloscope, and with good short-term efficacy. The complete regression of the diverticulum observed on Day 1 in 63 % of patients could be a marker of long-term clinical success.